2022
DOI: 10.1002/anie.202113204
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phosphoric Acid Catalyzed Conversion of Epoxides into Thiiranes: Mechanism, Stereochemical Model, and New Catalyst Design

Abstract: Computations and experiments leading to new chiral phosphoric acids (CPAs) for epoxide thionations are reported. Density functional theory calculations reveal the mechanism and origin of the enantioselectivity of such CPA‐catalyzed epoxide thionations. The calculated mechanistic information was used to design new efficient CPAs that were tested experimentally and found to be highly effective. Bulky ortho‐substituents on the 3,3′‐aryl groups of the CPA are important to restrict the position of the epoxide in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 84 publications
(9 reference statements)
0
17
0
Order By: Relevance
“…More recently, a DFT study of this reaction demonstrated the importance of sterically hindered ortho -substituents at the 3,3′-position of the aryl groups, as well as large para -substituents of the phosphoric acid catalyst, to improve the control of the enantioselectivity …”
Section: Kinetic Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a DFT study of this reaction demonstrated the importance of sterically hindered ortho -substituents at the 3,3′-position of the aryl groups, as well as large para -substituents of the phosphoric acid catalyst, to improve the control of the enantioselectivity …”
Section: Kinetic Resolutionmentioning
confidence: 99%
“…More recently, a DFT study of this reaction demonstrated the importance of sterically hindered ortho-substituents at the 3,3′position of the aryl groups, as well as large para-substituents of the phosphoric acid catalyst, to improve the control of the enantioselectivity. 82 In the same year, List and co-workers expanded the applicability of the self-assembled activation strategy of phosphoric acid with carboxylic acids in the kinetic resolution of racemic terminal epoxides (Scheme 8). 83 Specifically, benzoic acid was employed as the nucleophile, and more sterically demanding confined H 8 -BINOL-derived phosphoric acid 3c was used to promote the reaction.…”
Section: Kinetic Resolutionmentioning
confidence: 99%
“…Consequently, the stereostructure of thiiranes necessarily relies on the configuration of oxiranes. In a special case, it is possible to introduce a stereochemical element during the chalcogen substitution step via a kinetic resolution process as recently demonstrated by the List group utilizing the chiral phosphoric acid catalysis 39 , 40 . However, only terminal thiiranes can be prepared by this strategy.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, in 2016, List and coworkers described an organocatalytic synthesis of thiiranes from epoxides using a new thiolating reagent (Scheme 1G) [20a] . Earlier this year, in 2022, List, Houk, Lan and coworkers further studied this asymmetric reaction and probed its reaction mechanism [20b] …”
Section: Introductionmentioning
confidence: 99%